The Mechanism of Interactions on the Financial Market in Russia: Population and Financial Structures - ИвашиненкоНина Николаевна (Journal of Economic Sociology, 2010)
The paper gives a scheme of the financial population behavior research. The author analyzes the social-economic mechanism of the financial field as a system of elements and linkages, which provide the functioning and development of the financial sphere of the society. The paper discloses the results of the financial behavior research of the population in the Nizhegorodskiy region.